When home is elsewhere: housing policy challenges in the context of transit migration in Ghana and South Africa. Issue 1 (2nd January 2016) - Dick, Eva; Heitkamp, Thorsten
Abstract : In the last few years the relevance of transit migration was corroborated for many African countries. Oftentimes, it is related to urban migrants' subsisting linkages to their areas of origin, other times by the necessity or aspiration for onward journey. Based on recent research, this article examines the consequences of transit migration for the urban housing market and related challenges for sustainable housing policies in Ghana and South Africa. While in Ghana governmental housing hardly considers the urban poor, in South Africa a substantial post-apartheid subsidy system explicitly targets the lowest-income population. This article argues that neither approach adequately addresses transitory housing requirements related to mobility. Whereas the informal housing market can and often has responded with pragmatic solutions, it does not provide the maximum benefit to migrants. Therefore urban governments should enhance options in this increasingly important and highly dynamic housing sector recognising and enhancing informal approaches.